Design and optimization on training management system of professional classroom. Issue 1 (July 2021) - Sun, Xuwen; Qi, Lei; Li, Shixiong; Shan, Hongyan; Ma, Siming
Abstract: In order to further enrich the practical guarantee conditions of training theory teaching simulation in the university and improve the level of digital, scientific and information management of professional classrooms, this paper, through analyzing the ideas of system construction, explaining the system composition, structure and system function, designs a professional classroom training management system which integrates the functions of training design, training implementation, training assessment, etc., focally analyzes the key system technology and gives the technology as can be adopted next to further perfect the system function. The research is of great practical significance to improve the level of training information management system development and training management informatization subsequently.